2018
DOI: 10.1371/journal.pone.0194509
|View full text |Cite|
|
Sign up to set email alerts
|

Survival of viral pathogens in animal feed ingredients under transboundary shipping models

Abstract: The goal of this study was to evaluate survival of important viral pathogens of livestock in animal feed ingredients imported daily into the United States under simulated transboundary conditions. Eleven viruses were selected based on global significance and impact to the livestock industry, including Foot and Mouth Disease Virus (FMDV), Classical Swine Fever Virus (CSFV), African Swine Fever Virus (ASFV), Influenza A Virus of Swine (IAV-S), Pseudorabies virus (PRV), Nipah Virus (NiV), Porcine Reproductive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
246
2
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(284 citation statements)
references
References 29 publications
(35 reference statements)
11
246
2
5
Order By: Relevance
“…To what extent the specific composition of dog food creates a virucide environment for CSF virus has not been further elaborated in this study. In a recent study on the survival of pathogens in animal feeds, the pestivirus representative also could not be recovered from the wet or dry dog food used (Dee et al, ). The liquid absorption ability of plain sliced bread was ranked second from all the tested materials, and its ability to conserve the vaccine virus was superior to all other candidates.…”
Section: Discussionmentioning
confidence: 99%
“…To what extent the specific composition of dog food creates a virucide environment for CSF virus has not been further elaborated in this study. In a recent study on the survival of pathogens in animal feeds, the pestivirus representative also could not be recovered from the wet or dry dog food used (Dee et al, ). The liquid absorption ability of plain sliced bread was ranked second from all the tested materials, and its ability to conserve the vaccine virus was superior to all other candidates.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, ingredients should not be sourced from countries containing diseases absent in the country of the boar stud's location. Transboundary model studies showed significant risk due to extended survival times of certain viruses in various feed ingredients [30,31]. Soybean meal, in particular, seemed to support extended survival times for many viruses of concern as modeled for Foot and Mouth Disease (FMDV), African Swine Fever Virus (ASFV), Swine Vesicular Disease Virus (SVDV), Porcine Epidemic Diarrhea virus (PEDV), Vesicular Exanthema of Swine virus, Aujeszky's Disease, and PRRS.…”
Section: Feedmentioning
confidence: 99%
“…Complete feed and/or feed ingredients have been identified as potential routes of transmission for different emerging and reemerging viral pathogens, including porcine epidemic diarrhea virus (PEDV), classical swine fever virus (CSFV), African swine fever virus (ASFV) and porcine reproductive and respiratory syndrome virus (PRRSV) (Dee et al, , ). Additionally, SVV was shown to be a virus with a high degree of stability in different feed ingredients (Dee et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Complete feed and/or feed ingredients have been identified as potential routes of transmission for different emerging and reemerging viral pathogens, including porcine epidemic diarrhea virus (PEDV), classical swine fever virus (CSFV), African swine fever virus (ASFV) and porcine reproductive and respiratory syndrome virus (PRRSV) (Dee et al, , ). Additionally, SVV was shown to be a virus with a high degree of stability in different feed ingredients (Dee et al, ). Based on the recent outbreaks of SVV‐associated vesicular disease in finishing and farrowing pigs, as well as the increased rates of diarrhea and sudden death in newborn piglets associated with the infection in late 2018 (Leme et al, ), concerns were raised regarding the level of pig food safety and the possibility of feed and feed supplies being related to the increase in the disease occurrence.…”
Section: Introductionmentioning
confidence: 99%